CuS-131I-PEG Nanotheranostics-Induced "Multiple Mild-Hyperthermia" Strategy to Overcome Radio-Resistance in Lung Cancer Brachytherapy - Yanna Cui; Hui Yan; Haoze Wang; Yongming Zhang; Meng Li; Kai Cui; Zeyu Xiao; Liu Liu; Wenhui Xie (MDPI AG, 2022)
Brachytherapy is one mainstay treatment for lung cancer. However, a great challenge in brachytherapy is radio-resistance, which is caused by severe hypoxia in solid tumors. In this research, we have developed a PEGylated 131I-labeled CuS nanotheranostics (CuS-131I-PEG)-induced "multiple mild-hyperthermia" strategy to reverse hypoxia-associated radio-resistance. Specifically, after being injected with CuS-131I-PEG nanotheranostics, tumors were irradiated by NIR laser to mildly increase tumor temperature (39~40 °C). This mild hyperthermia can improve oxygen levels and reduce expression of hypoxia-induced factor-1α (HIF-1α) inside tumors, which brings about alleviation of tumor hypoxia and reversion of hypoxia-induced radio-resistance. During the entire treatment, tumors are treated by photothermal brachytherapy three times, and meanwhile mild hyperthermia stimulation is conducted before each treatment of photothermal brachytherapy, which is defined as a "multiple mild-hyperthermia" strategy. Based on this strategy, tumors have been completely inhibited. Overall, our research presents a simple and effective "multiple mild-hyperthermia" strategy for reversing radio-resistance of lung cancer, achieving the combined photothermal brachytherapy.